Low-carbon gold tailing-based ultra-high-performance concrete material suitable for steep-gradient pavement and preparation method of low-carbon gold tailing-based ultra-high-performance concrete material

By using multi-stage gold tailings, machined sand and low-carbon gelling materials, combined with composite external dopants and steel fibers, a tightly packed structure is formed, which solves the fluidity and strength problems of ultra-high-performance concrete in large-slope pavement applications, and achieves high-performance concrete material preparation.

CN120554080AActive Publication Date: 2025-08-29SHANDONG HI SPEED CONSTRUCTION MANAGEMENT GROUP CO LTD +2

Patent Information

Application Number
CN202511055503.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-08-29
Estimated Expiration
2045-07-30

AI Technical Summary

Technical Problem

In the application of large slope pavement, existing ultra-high performance concrete has problems such as low tensile strength, poor toughness, high flow expansion of mixing materials and difficult to control. During the preparation process, gold tailings have problems such as low compression, flexural and tensile strength caused by the insemination of close packing theory, metal impurities interfere with fiber bonding and high microporosity.

Method used

Multi-stage gold tailings and machined sand are used to replace traditional quartz sand, and low-carbon gelling materials are prepared using bulk solid waste and limited early strength exciters. Combined with composite external dopants and steel fibers, a tightly packed structure of nano- and sub-microns are formed. The micropores are filled with nano-materials and bubbles are introduced to improve the plasticity of the mixture.

Benefits of technology

Low-cost, environmentally friendly ultra-high performance concrete materials were prepared, which had high compressive strength, high flexural strength, high toughness, excellent freezing resistance and chloride ion permeability, and met the requirements of on-site casting of large slope pavements. The compressive strengths of 7 d and 28 d were greater than 70 MPa and 120 MPa, respectively, the flexural strengths were greater than 9 MPa and 17 MPa, the flow expansion degree was less than 300 mm, the chloride ion permeability was ≤2.0×10-13 m2/s, and the freezing resistance was > F500.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of ultra-high-performance concrete materials, in particular to a low-carbon gold tailing-based ultra-high-performance concrete material suitable for a large-gradient pavement and a preparation method of the low-carbon gold tailing-based ultra-high-performance concrete material. According to the invention, the multi-stage gold tailings and the machine-made sand are adopted to replace quartz sand in a traditional ultra-high performance concrete material, and a low-carbon cementing material prepared from a large amount of solid waste and a limited early strength activator is adopted to replace traditional high-grade cement with a large mixing amount and is cooperated with a composite admixture and steel fibers; and the low-cost and environment-friendly ultra-high performance concrete material is prepared. The ultrahigh concrete material prepared by the invention has high compressive strength, high breaking strength, high toughness and excellent freezing resistance and chloride ion permeability resistance, and also has the performance of autonomously expanding flow, thereby meeting the construction requirements of cast-in-place of ultrahigh-performance concrete in a large-gradient pavement scene.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high performance concrete materials, and in particular to a low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads and a preparation method thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance understanding of the overall background of the invention and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to those skilled in the art.

[0003] Currently, conventional concrete suffers from shortcomings such as low tensile strength, poor toughness, and the inability to effectively control crack growth after initiation. These shortcomings lead to premature deterioration of concrete structures, rendering them unusable and significantly reducing their durability and service life. To overcome these shortcomings, ultra-high performance concrete (UHPC) has been proposed and applied. UHPC is a cement-based material that utilizes the close-packing theory of particles, fracture mechanics, and micromechanics to systematically design, optimize, and adjust the material system, adding fibers at a volume fraction of 1-3%. UHPC significantly improves concrete's tensile and shear resistance, resulting in excellent toughness and the ability to effectively control the development of concrete cracks. It is now gradually being applied in practical projects.

[0004] However, due to the lack of coarse aggregate in ultra-high performance concrete, the flow expansion of the mixture is high and difficult to control, which restricts its application in special scenarios such as cast-in-place large-slope pavements.

[0005] Gold tailings, meanwhile, are solid waste discharged after gold or other useful components are recovered from gold ore through beneficiation or gold extraction processes. Containing over 80% inorganic minerals such as silica and aluminum oxides, their composition is similar to that of many building materials, making them theoretically suitable for use in the production of engineering materials. However, the preparation of ultra-high-performance concrete (UHPC) from gold tailings presents the following challenges: The particle distribution of the tailings deviates from the tight packing theory required for UHPC; metallic impurities in the tailings may interfere with the bonding of steel fibers; and the high microporosity of the gold tailings results in low compressive, flexural, and tensile strengths of the concrete material. Furthermore, the high microporosity of the gold tailings compromises the frost resistance and chloride ion permeability of the UHPC. Summary of the Invention

[0006] In order to overcome the above problems, the present invention provides a low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads and a preparation method thereof.

[0007] In order to achieve the above technical objectives, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a low-carbon gold tailings-based ultra-high performance concrete material suitable for steeply sloped roads. The raw materials include, by weight, 100 parts of solid waste cementitious material, 50-150 parts of multi-grade gold tailings, 50-150 parts of machine-made sand, 0.3-1.5 parts of composite admixture, 3-10 parts of steel fiber, and 40-80 parts of water. The solid waste cementitious material comprises an alkaline solid waste activator-activated matrix material and an early strength activator; the alkaline solid waste activator-activated matrix material is composed of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume; the early strength activator is composed of sodium sulfate, calcium oxide and nanomaterials; The multi-grade gold tailings include coarse-grade tailings and fine-grade tailings, wherein the coarse-grade gold tailings have a particle size of 0.6 mm to 2 mm and a moisture content of less than 5%; the fine-grade gold tailings have a particle size of less than 0.6 mm and a moisture content of less than 15%; The composite external admixture consists of polycarboxylate water reducer, fatty alcohol polyoxyethylene ether sodium sulfate, maltitol and hydroxypropyl methylcellulose.

[0008] In one or more embodiments, the mass ratio of the alkaline solid waste activator to the matrix material is (200-300):1. Because the early strength activator contains sulfate, if the amount of the alkaline solid waste activator to the matrix material is too small, the activation effect is not obvious; if the amount is too high, an alkali-aggregate reaction will occur, which will adversely affect the volume stability of the concrete.

[0009] In one or more embodiments, in the matrix material excited by the alkaline solid waste activator, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1:(2~4):(1~3):(1~3):(0.3~0.8):(0.5~1).

[0010] In one or more embodiments, the alkaline solid waste activator activates the matrix material, and the specific surface area of ​​the cement clinker is greater than 350 m 2 / kg; In one or more embodiments, the slag in the matrix material excited by the alkaline solid waste activator is of grade S95 or above; In one or more embodiments, the CaSO4 content in the fluorgypsum in the matrix material excited by the alkaline solid waste activator is higher than 85%.

[0011] In one or more embodiments, the mass ratio of sodium sulfate, calcium oxide, and nanomaterial in the early strength activator is 1:(0.5-3):(0.5-3). At this ratio, the early strength activator has the best stimulating effect.

[0012] In one or more embodiments, the nanomaterial in the early strength activator is one or more of nano-silicon dioxide, nano-titanium dioxide, and nano-calcium carbonate; the particle size of the nanomaterial is less than 100 nm. Nanomaterials have high hydration activity and can synergize with other components in the early strength activator to improve the early strength of solid waste cementitious materials.

[0013] In one or more embodiments, the mass ratio of coarse-grained tailings to coarse-grained tailings in the multi-graded gold tailings is 1:(0.5-1.5). Multi-graded gold tailings facilitate the formation of a densely packed structure within the ultra-high performance concrete (UHPC) matrix. The coarse-grained tailings within the multi-graded gold tailings serve as the basic framework, while the coarse-grained tailings and the adhesive fill the voids within the framework, making the entire matrix more compact. Furthermore, under this defined ratio, a dense structure is more easily formed without significantly weakening the strength of the UHPC.

[0014] In one or more embodiments, the manufactured sand has a particle size of less than 2.36 mm and a fines content of less than 8%. Large aggregates in ultra-high performance concrete can significantly reduce the toughness of the concrete, while high fines content can significantly increase the material's viscosity, hindering on-site construction.

[0015] In one or more embodiments, the mass ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture is 1300:(1-5):(1-5):(5-20). In the composite admixture, the polycarboxylate water-reducing agent acts as a water reducer, effectively reducing the water-binder ratio of the material; the sodium fatty alcohol polyoxyethylene ether sulfate acts as an air entrainer, reducing the viscosity of low-flow concrete mixtures by introducing tiny bubbles; the maltitol primarily acts as a retarding agent; and the hydroxypropyl methylcellulose acts as a water retainer and increases the thixotropy of the mixture, reducing the fluidity of the material.

[0016] In one or more embodiments, the viscosity of hydroxypropyl methylcellulose is 100,000 to 300,000 N / A. Within this viscosity range, the amount of hydroxypropyl methylcellulose is easy to control and the cost is lower.

[0017] In one or more embodiments, the steel fiber has a length of 8 to 15 mm and a diameter of 0.18 to 0.25 mm.

[0018] A second aspect of the present invention provides a method for preparing the low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads as described in the first aspect, comprising the following steps: Solid waste cementitious materials, multi-level gold tailings, machine-made sand, and composite admixtures are dry-premixed, water is added for a first stirring, and then steel fibers are added for a second stirring to obtain the low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads.

[0019] In one or more embodiments, the preparation of solid waste gelling material comprises the following steps: (1) Sodium sulfate, calcium oxide and nanomaterials are weighed in proportion and ball-milled to obtain an early strength activator; (2) Cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume as well as the early strength activator in step (1) are weighed in proportion and ball-milled to obtain a solid waste cementitious material.

[0020] Preferably, in step (1), the ball milling speed is 100-200 r / min, and the ball milling time is 10-15 min. Low-speed ball milling can reduce heat generation during the ball milling process and prevent the system from overheating and causing the early strength activator to fail.

[0021] Preferably, in step (2), the mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume need to be dried before ball milling, the drying temperature is 60-95°C, and the drying time is not less than 24 hours.

[0022] Preferably, in step (2), the ball milling speed is 400-500 r / min, and the ball milling time is 20-30 min.

[0023] Preferably, in step (2), the specific surface area of ​​the solid waste gelling material is greater than 450 m 2 / kg.

[0024] In one or more embodiments, the preparation of the composite admixture comprises the following steps: The polycarboxylate water reducer and sodium polyoxyethylene fatty alcohol ether sulfate are weighed in proportion, dispersed in deionized water, fully mixed, dried, and the solid is collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion, and ball milled to obtain a composite admixture.

[0025] Preferably, the thorough mixing is carried out by stirring at a speed of 150 to 300 r / min and a stirring time of 20 to 40 min.

[0026] Preferably, the drying temperature is 55-65° C. and the drying time is at least 24 h.

[0027] Preferably, the ball milling speed is 100-200 r / min, and the ball milling time is 10-15 min.

[0028] In one or more embodiments, the premixing time is 3 to 6 minutes, and the rotation speed is 40 to 60 r / min; In one or more embodiments, the first stirring time is 6 to 8 minutes, and the rotation speed is 40 to 60 r / min; In one or more embodiments, the second stirring time is 2 to 3 minutes, and the rotation speed is 40 to 60 r / min; The beneficial effects of the present invention are: (1) The present invention uses multi-level gold tailings and machine-made sand to replace the quartz sand in traditional ultra-high performance concrete materials, uses low-carbon cementitious materials prepared from bulk solid waste and limited early strength activators to replace traditional high-grade cement with large amounts of admixtures, and synergistically uses composite admixtures and steel fibers to prepare low-cost, environmentally friendly ultra-high performance concrete materials. The ultra-high performance concrete material prepared by the present invention has high compressive strength, high flexural strength, high toughness, and excellent frost resistance and chloride ion permeability resistance. It also has the performance of involuntary expansion and flow, meeting the construction requirements of ultra-high performance concrete for on-site pouring in large-slope road scenarios. Specifically, the ultra-high performance concrete material prepared by the present invention has a 7-day and 28-day compressive strength greater than 70 MPa and 120 MPa, respectively, and a 7-day and 28-day flexural strength greater than 9 MPa and 17 MPa, respectively; the flow expansion is less than 300 mm, the slump is less than 65 mm, and the chloride ion permeability resistance (RCM method) is ≤2.0×10 -13 m 2 / s, antifreeze performance>F500.

[0029] (2) The present invention adopts a low-alkalinity early strength agent as a precursor material. The active components in the precursor material release ions that promote hydration. The dissolved silicon and aluminum species are recombined in the alkaline solution and form a gel phase with a three-dimensional network structure through a condensation reaction. The gel phase continuously cross-links the gel network to fill the pores. The nanoparticles gradually densify during the aggregation process. Combined with the composite admixture, the water demand of the material is significantly reduced. The multiple components work synergistically under the set ratio, so that low-cost and low-carbon adhesives can also obtain the mechanical properties of ultra-high performance concrete.

[0030] (3) In the present invention, multi-level gold tailings are used as the main aggregate system, combined with machine-made sand to form a submicron and millimeter-scale dense stacking. At the same time, nanomaterials and ultrafine powder materials are introduced to construct a nanoscale and submicron-scale dense stacking structure, so that the low-carbon gold tailings-based concrete prepared by the present invention meets the dense stacking structure of ultra-high performance concrete materials. In addition, nanomaterials significantly improve the mechanical properties, durability and functionality of the material through unique size effects and surface effects. Nanoparticles fill the micropores and interfacial transition zone (ITZ) in the cement matrix, reduce porosity, increase density, and react with cement hydration product Ca(OH)2 to generate more CSH gel, significantly improving mechanical properties. At the same time, nanomaterials fill the capillary channels and micropores of gold tailings, reduce the penetration of corrosive media such as chloride ions and sulfates, reduce frost heave pressure, and extend the life of the structure.

[0031] (4) In the present invention, sodium sulfate of fatty alcohol polyoxyethylene ether is used to introduce nano-scale closed bubbles to improve the plasticity of the mixture, and hydroxypropyl methylcellulose is used to improve the cohesiveness of the mixture. The two cooperate with each other to ensure that the ultra-high performance concrete has the performance of almost involuntary expansion and flow without the addition of coarse aggregate, thus meeting the construction requirements of on-site pouring of ultra-high performance concrete in large-slope road scenarios. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are exemplary and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, they indicate the presence of features, steps, operations, devices, components and / or combinations thereof.

[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0035] The chemical compositions of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume and multi-stage gold tailings in the following examples are shown in Table 1.

[0036] In the following examples, the coarse-grained gold tailings have a particle size of 0.6 mm to 2 mm and a moisture content of 3.7%, while the fine-grained gold tailings have a particle size of less than 0.6 mm and a moisture content of 12.1%. The particle size of machine-made sand is less than 2.36 mm, and the powder content is less than 8%; The viscosity of hydroxypropyl methylcellulose is 150,000; The length of the steel fiber is 10 mm and the diameter is 0.20 mm.

[0037] Table 1 Chemical compositions of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume, and multi-stage gold tailings

[0038] Example 1 A low-carbon gold tailings-based ultra-high performance concrete material suitable for steeply sloped roads, the raw materials of which include, by weight, 100 parts of solid waste cementitious material, 50 parts of multi-grade gold tailings, 150 parts of machine-made sand, 0.3 parts of composite admixture, 3 parts of steel fiber, and 45.5 parts of water; In the solid waste cementitious material, the mass ratio of the matrix material activated by the alkaline solid waste activator and the early strength activator is 200:1; in the matrix material activated by the alkaline solid waste activator, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1:2:1:3:0.3:0.5; in the early strength activator, the mass ratio of sodium sulfate, calcium oxide and nanomaterial is 1:0.5:3; In the multi-grade gold tailings, the mass ratio of coarse-grained tailings to fine-grained tailings is 1:0.5.

[0039] In the composite admixture, the mass ratio of polycarboxylate water reducer, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol and hydroxypropyl methylcellulose is 1300:1:5:5.

[0040] Preparation of low-carbon gold tailings-based ultra-high performance concrete materials suitable for steep slope roads: Sodium sulfate, calcium oxide and nanomaterials were weighed in proportion and placed in a ball mill for sealed low-speed grinding for 10 minutes, with the ball mill speed maintained at 100 r / min to obtain an early strength activator. The mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume were dried at 60 °C (drying time was not less than 24 h), and then the dried mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume, cement clinker and early strength activator were weighed in proportion and placed in a ball mill for sealed grinding for 20 min. The ball mill speed was maintained at 400 r / min to obtain a solid waste cementitious material with a specific surface area of ​​495 m 2 / kg; The polycarboxylate water reducer and sodium polyoxyethylene fatty alcohol ether sulfate were weighed in proportion and dispersed in 500 mL of deionized water. The mixture was stirred at 150 r / min for 20 min. The mixture was dried at 55°C (drying time was not less than 24 h). The solid was collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion, and ball milled to obtain a powdered composite admixture. Solid waste cementitious materials, multi-grade gold tailings, machine-made sand, and composite admixtures were premixed at 40 r / min for 3 min; water was added for the first stirring, the stirring time was 6 min, and the speed was maintained at 40 r / min; then steel fiber was added for the second stirring, the stirring time was 2 min, and the speed was maintained at 40 r / min. A low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads was obtained.

[0041] Example 2 A low-carbon gold tailings-based ultra-high performance concrete material suitable for steeply sloped roads, the raw materials of which include, by weight, 100 parts of solid waste cementitious material, 70 parts of multi-grade gold tailings, 130 parts of machine-made sand, 0.6 parts of composite admixture, 4.5 parts of steel fiber, and 51.9 parts of water; In the solid waste cementitious material, the mass ratio of the matrix material activated by the alkaline solid waste activator and the early strength activator is 220:1; in the matrix material activated by the alkaline solid waste activator, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1:2.5:1.5:3:0.4:0.6; in the early strength activator, the mass ratio of sodium sulfate, calcium oxide and nanomaterial is 1:0.5:2; In the multi-grade gold tailings, the mass ratio of coarse-grained tailings to fine-grained tailings is 1:0.7.

[0042] In the composite admixture, the mass ratio of polycarboxylate water reducer, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol and hydroxypropyl methylcellulose is 1300:2:4:10.

[0043] Preparation of low-carbon gold tailings-based ultra-high performance concrete materials suitable for steep slope roads: Sodium sulfate, calcium oxide and nanomaterials were weighed in proportion and placed in a ball mill for sealed low-speed grinding for 10 minutes, with the ball mill speed maintained at 200 r / min to obtain an early strength activator. Mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume were dried at 60 °C (drying time was not less than 24 h), and then the dried mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume, cement clinker and early strength activator were weighed in proportion and placed in a ball mill for sealed grinding for 20 min. The ball mill speed was maintained at 400 r / min to obtain a solid waste cementitious material. The specific surface area of ​​the material was measured to be 490 m 2 / kg; Polycarboxylate water reducer and sodium fatty alcohol polyoxyethylene ether sulfate were weighed in proportion and dispersed in 500 mL of deionized water. The mixture was stirred at 150 r / min for 20 min and dried at 65°C (drying time was not less than 24 h). The solid was collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion, and ball milled to obtain a powdered composite admixture. Solid waste cementitious materials, multi-grade gold tailings, machine-made sand, and composite admixtures were premixed at 40 r / min for 3 min; water was added for the first stirring, the stirring time was 6 min, and the speed was maintained at 40 r / min; then steel fiber was added for the second stirring, the stirring time was 2 min, and the speed was maintained at 40 r / min. A low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads was obtained.

[0044] Example 3 A low-carbon gold tailings-based ultra-high performance concrete material suitable for steeply sloped roads, the raw materials of which include, by weight, 100 parts of solid waste cementitious material, 90 parts of multi-grade gold tailings, 110 parts of machine-made sand, 0.9 parts of composite admixture, 6 parts of steel fiber, and 58.3 parts of water; In the solid waste cementitious material, the mass ratio of the alkaline solid waste activator-activated matrix material and the early strength activator is 240:1; in the alkaline solid waste activator-activated matrix material, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1:3:2:2.5:0.5:0.7; in the early strength activator, the mass ratio of sodium sulfate, calcium oxide and nanomaterials is 1:1.5:2.

[0045] In the multi-grade gold tailings, the mass ratio of coarse-grained tailings to fine-grained tailings is 1:0.9.

[0046] In the composite admixture, the mass ratio of polycarboxylate water reducer, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol and hydroxypropyl methylcellulose is 1300:3:3:15.

[0047] Preparation of low-carbon gold tailings-based ultra-high performance concrete materials suitable for steep slope roads: Sodium sulfate, calcium oxide and nanomaterials were weighed in proportion and placed in a ball mill for sealed low-speed grinding for 10 minutes, with the ball mill speed maintained at 100 r / min to obtain an early strength activator. Mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume were dried at 60 °C (drying time was not less than 24 h), and then the dried mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume, cement clinker and early strength activator were weighed in proportion and placed in a ball mill for sealed grinding for 20 min. The ball mill speed was maintained at 500 r / min to obtain a solid waste cementitious material. The specific surface area of ​​the material was measured to be 491 m 2 / kg; The polycarboxylate water reducer and sodium polyoxyethylene fatty alcohol ether sulfate were weighed in proportion and dispersed in 500 mL of water. The mixture was stirred at 150 r / min for 20 min. The mixture was dried at 55°C (drying time was not less than 24 h). The solid was collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion. The powdered composite admixture was obtained by ball milling. Solid waste cementitious materials, multi-grade gold tailings, machine-made sand, and composite admixtures were premixed at 40 r / min for 3 min; water was added for the first stirring, the stirring time was 6 min, and the speed was maintained at 40 r / min; then steel fiber was added for the second stirring, the stirring time was 2 min, and the speed was maintained at 40 r / min. A low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads was obtained.

[0048] Example 4 A low-carbon gold tailings-based ultra-high performance concrete material suitable for steeply sloped roads, the raw materials of which include, by weight, 100 parts of solid waste cementitious material, 110 parts of multi-grade gold tailings, 90 parts of machine-made sand, 1.2 parts of composite admixture, 7.5 parts of steel fiber, and 64.8 parts of water; In the solid waste cementitious material, the mass ratio of the alkaline solid waste activator-activated matrix material and the early strength activator is 260:1; in the alkaline solid waste activator-activated matrix material, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1:3.5:2.5:2:0.6:0.8; in the early strength activator, the mass ratio of sodium sulfate, calcium oxide and nanomaterials is 1:2:1.5.

[0049] In the multi-grade gold tailings, the mass ratio of coarse-grained tailings to fine-grained tailings is 1:1.1.

[0050] In the composite admixture, the mass ratio of polycarboxylic acid water reducer, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol and hydroxypropyl methylcellulose is 1300:4:2:20.

[0051] Preparation of low-carbon gold tailings-based ultra-high performance concrete materials suitable for steep slope roads: Sodium sulfate, calcium oxide and nanomaterials were weighed in proportion and placed in a ball mill for sealed low-speed grinding for 10 minutes, with the ball mill speed maintained at 100 r / min to obtain an early strength activator. Mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume were dried at 60 °C (drying time was not less than 24 h), and then the dried mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume, cement clinker and early strength activator were weighed in proportion and placed in a ball mill for sealed grinding for 20 min. The ball mill speed was maintained at 400 r / min to obtain a solid waste cementitious material. The specific surface area of ​​the material was measured to be 492 m 2 / kg; Polycarboxylate water reducer and sodium fatty alcohol polyoxyethylene ether sulfate were weighed in proportion and dispersed in 500 mL of deionized water. The mixture was stirred at 150 r / min for 30 min and dried at 55°C (drying time was not less than 24 h). The solid was collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion, and ball milled to obtain a powdered composite admixture. Solid waste cementitious materials, multi-grade gold tailings, machine-made sand, and composite admixtures were premixed at 40 r / min for 3 min; water was added for the first stirring, the stirring time was 6 min, and the speed was maintained at 40 r / min; then steel fiber was added for the second stirring, the stirring time was 2 min, and the speed was maintained at 40 r / min. A low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads was obtained.

[0052] Example 5 A low-carbon gold tailings-based ultra-high performance concrete material suitable for steeply sloped roads, the raw materials of which include, by weight, 100 parts of solid waste cementitious material, 130 parts of multi-grade gold tailings, 70 parts of machine-made sand, 1.5 parts of composite admixture, 9 parts of steel fiber, and 71.4 parts of water; In the solid waste cementitious material, the mass ratio of the alkaline solid waste activator-activated matrix material and the early strength activator is 280:1; in the alkaline solid waste activator-activated matrix material, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1:4:3:1.5:0.7:0.9; in the early strength activator, the mass ratio of sodium sulfate, calcium oxide and nanomaterials is 1:2.5:1.

[0053] In the multi-grade gold tailings, the mass ratio of coarse-grained tailings to fine-grained tailings is 1:1.3.

[0054] In the composite admixture, the mass ratio of polycarboxylate water reducer, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol and hydroxypropyl methylcellulose is 1300:5:1:5.

[0055] Preparation of low-carbon gold tailings-based ultra-high performance concrete materials suitable for steep slope roads: Sodium sulfate, calcium oxide and nanomaterials were weighed in proportion and placed in a ball mill for sealed low-speed grinding for 10 minutes, with the ball mill speed maintained at 100 r / min to obtain an early strength activator. Mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume were dried at 60 °C (drying time was not less than 24 h), and then the dried mineral powder, steel slag powder, fly ash, fluorgypsum, silica fume, cement clinker and early strength activator were weighed in proportion and placed in a ball mill for sealed grinding for 20 min. The ball mill speed was maintained at 400 r / min to obtain a solid waste cementitious material with a measured specific surface area of ​​489 m 2 / kg; Polycarboxylate water reducer and sodium fatty alcohol polyoxyethylene ether sulfate were weighed in proportion and dispersed in 500 mL of deionized water. The mixture was stirred at 150 r / min for 40 min and dried at 65°C (drying time was not less than 24 h). The solid was collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion, and ball milled to obtain a powdered composite admixture. Solid waste cementitious materials, multi-grade gold tailings, machine-made sand, and composite admixtures were premixed at 40 r / min for 3 min; water was added for the first stirring, the stirring time was 6 min, and the speed was maintained at 40 r / min; then steel fiber was added for the second stirring, the stirring time was 2 min, and the speed was maintained at 40 r / min. A low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads was obtained.

[0056] Comparative Example 1 Compared with Example 1, the solid waste cementitious material was replaced with ordinary Portland cement (P·O 52.5 cement), and the other components and preparation method were the same as those in Example 1.

[0057] Comparative Example 2 Compared with Example 1, only the ratio of the alkaline solid waste activator to the matrix material and the early strength activator in the solid waste gelling material was adjusted. The addition ratio of the early strength activator in this comparative example was 0.

[0058] Comparative Example 3 Compared with Example 1, only the ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum, and silica fume in the matrix material excited by the alkaline solid waste activator was adjusted. In this comparative example, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum, and silica fume in the excited matrix material was 0:1:2:1:3:0.3:0.5.

[0059] Comparative Example 4 Compared with Example 1, only the ratio of sodium sulfate, calcium oxide and nanomaterial in the early strength activator was adjusted. The mass ratio of sodium sulfate, calcium oxide and nanomaterial in this comparative example was 0.5:0.25:5.

[0060] Comparative Example 5 Compared with Example 1, only the ratio of coarse-grained gold tailings to fine-grained gold tailings in the multi-grade gold tailings was adjusted. The mass ratio of coarse-grained gold tailings to fine-grained gold tailings in the multi-grade gold tailings of this comparative example was 1:3.

[0061] Comparative Example 6 Compared with Example 1, only the ratio of coarse-grained gold tailings to fine-grained gold tailings in the multi-grade gold tailings was adjusted. The mass ratio of coarse-grained gold tailings to fine-grained gold tailings in the multi-grade gold tailings of this comparative example was 1:0.25.

[0062] Comparative Example 7 Compared with Example 1, only coarse-grained gold tailings are contained. Other ingredients and preparation methods are the same as those in Example 1.

[0063] Comparative Example 8 Compared with Example 1, only fine-grained gold tailings are contained. Other ingredients and preparation methods are the same as those in Example 1.

[0064] Comparative Example 9 Compared with Example 1, no machine-made sand was added, and all aggregates were multi-grade gold tailings with the same proportion as in Example 1.

[0065] Comparative Example 10 Compared with Example 1, only the ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture was adjusted. The mass ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture of this comparative example was 1300:0.5:0.5:10.

[0066] Comparative Example 11 Compared with Example 1, Sika 556P water reducer is used instead of the composite admixture.

[0067] Comparative Example 12 Compared with Example 1, only the ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture was adjusted. The mass ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture of this comparative example was 0:2.5:2.5:10.

[0068] Comparative Example 13 Compared with Example 1, only the ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture was adjusted. The mass ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture of this comparative example was 1300:0:2.5:10.

[0069] Comparative Example 14 Compared with Example 1, only the ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture was adjusted. The mass ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture of this comparative example was 1300:2.5:0:10.

[0070] Comparative Example 15 Compared with Example 1, only the ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture was adjusted. The mass ratio of polycarboxylate water-reducing agent, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol, and hydroxypropyl methylcellulose in the composite admixture of this comparative example was 1300:2.5:2.5:0.

[0071] Comparative Example 16 Compared with Example 1, only the amount of water added was adjusted, and this comparative example contained 100 parts of water.

[0072] Comparative Example 17 The difference between Comparative Example 2 of the present invention and Example 1 is that the cementitious material used is commercial cement powder, and no solid waste cementitious material is used.

[0073] Performance testing: The concrete materials prepared in Examples 1 to 5 and Comparative Examples 1 to 17 were tested for mechanical properties, flow expansion, slump, frost resistance, and chloride ion permeability resistance in accordance with JC / T 3420-2020 "Test Procedures for Cement and Cement Concrete in Highway Engineering". The performance indicators are shown in Table 2 below. Chloride ion permeability resistance (RCM method) ≤5.0×10 -13 m 2 / s Table 2 Performance test results of concrete materials prepared in Examples 1 to 5 and Comparative Examples 1 to 16

[0074] As shown in Table 2, the low-carbon gold tailings ultra-high performance concrete materials for steep slope roads prepared in Examples 1 to 5 have 7-day and 28-day compressive strengths greater than 70 MPa and 120 MPa, respectively, and 7-day and 28-day flexural strengths greater than 9 MPa and 17 MPa, respectively. The flow expansion is less than 300 mm, the slump is less than 65 mm, and the chloride ion penetration resistance (RCM method) is ≤2.0×10 - 13 m 2 / s, frost resistance > F500. This meets the requirements for RPC100 strength grade concrete in GB / T 31387-2015, "Reactive Powder Concrete." Comparative Example 1 also reveals that the mechanical properties and durability of ultra-high performance concrete prepared using the low-carbon cementitious material of the present invention are essentially comparable to those of ordinary Portland cement containing P·O 52.5 cement, and far exceed those of commercially available low-carbon cementitious materials (Comparative Example 17). In Comparative Example 2, no early strength agent was added, and the final cementitious material strength was significantly lower than the test results in the Examples, demonstrating that early strength agents significantly enhance the mechanical and durability properties of ultra-high performance concrete. Adjusting the binder ratio also significantly reduces the mechanical strength of the ultra-high performance concrete, demonstrating that ideal mechanical properties can only be achieved using the binder ratio of the present invention. By adjusting the coarse-to-fine ratio of multi-grade gold tailings, it was found that the mechanical properties and early working performance of the ultra-high performance concrete were weakened to varying degrees, with some even failing to meet engineering requirements. Furthermore, by replacing the composite early-strength admixture or adjusting the ratio of its components, it was found that the mechanical properties and early working performance of the ultra-high performance concrete also decreased to varying degrees, demonstrating that the water-reducing, retarding, air-entraining, and thickening components in the composite admixture are essential. Simultaneously, increasing the amount of water added to the material significantly reduced the mechanical properties of the ultra-high performance concrete, while its flow expansion and slump increased significantly, no longer meeting the technical requirements for cast-in-place concrete construction on steeply sloped pavements. This demonstrates that the material of the present invention performs optimally only when the designed amount of water is added.

[0075] In summary, the low-carbon gold tailings ultra-high performance concrete material of the present invention is used to simultaneously meet the requirements of ultra-high mechanical properties and the construction requirements of ultra-low flow expansion of materials under large-slope road surfaces.

[0076] The foregoing description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art will readily appreciate that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention are intended to be within the scope of protection of the present invention.

Claims

1. A low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads, characterized in that: The raw materials include, by weight: 100 parts of solid waste cementitious materials, 50-150 parts of multi-grade gold tailings, 50-150 parts of machine-made sand, 0.3-1.5 parts of composite admixture, 3-10 parts of steel fiber and 40-80 parts of water; The solid waste cementitious material comprises an alkaline solid waste activator-activated matrix material and an early strength activator; the alkaline solid waste activator-activated matrix material is composed of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume; the early strength activator is composed of sodium sulfate, calcium oxide and nanomaterials; The multi-grade gold tailings include coarse-grained tailings and fine-grained tailings, wherein the coarse-grained gold tailings have a particle size of 0.6 mm to 2 mm and a moisture content of less than 5%; the fine-grained gold tailings have a particle size of less than 0.6 mm and a moisture content of less than 15%; The composite external admixture consists of polycarboxylic acid water reducer, fatty alcohol polyoxyethylene ether sodium sulfate, maltitol and hydroxypropyl methylcellulose.

2. The low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads according to claim 1, characterized in that: The mass ratio of the alkaline solid waste activator to the matrix material and the early strength activator is (200~300):1; In the matrix material activated by the alkaline solid waste activator, the mass ratio of cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume is 1: (2-4): (1-3): (1-3): (0.3-0.8): (0.5-1); In the early strength activator, the mass ratio of sodium sulfate, calcium oxide and nanomaterials is 1: (0.5~3): (0.5~3); In the early strength activator, the nano material is one or more of nano silicon dioxide, nano titanium dioxide and nano calcium carbonate, and the particle size of the nano material is less than 100 nm.

3. The low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads according to claim 1, characterized in that: In multi-grade gold tailings, the mass ratio of coarse-grained tailings to fine-grained tailings is 1:(0.5~1.5).

4. The low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads according to claim 1, characterized in that: The particle size of machine-made sand is less than 2.36 mm, and the powder content is less than 8%.

5. The low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads according to claim 1, characterized in that: In the composite admixture, the mass ratio of polycarboxylate water reducer, sodium fatty alcohol polyoxyethylene ether sulfate, maltitol and hydroxypropyl methylcellulose is: 1300: (1-5): (1-5): (5-20); The viscosity of hydroxypropyl methylcellulose is 100,000~300,000.

6. The method for preparing a low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads according to any one of claims 1 to 5, characterized in that: The steps include: Solid waste cementitious materials, multi-level gold tailings, machine-made sand, and composite admixtures are dry-premixed, water is added for a first stirring, and then steel fibers are added for a second stirring to obtain the low-carbon gold tailings-based ultra-high performance concrete material suitable for steep slope roads.

7. The preparation method according to claim 6, wherein The preparation of solid waste cementitious materials includes the following steps: (1) Sodium sulfate, calcium oxide and nanomaterials are weighed in proportion and ball-milled to obtain an early strength activator; (2) Cement clinker, mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume as well as the early strength activator in step (1) are weighed in proportion and ball-milled to obtain a solid waste cementitious material.

8. The preparation method according to claim 7, wherein In step (1), the ball milling speed is 100-200 r / min, and the ball milling time is 10-15 min; In step (2), the mineral powder, steel slag powder, fly ash, fluorgypsum and silica fume need to be dried before ball milling. The drying temperature is 60-95 °C and the drying time is not less than 24 h. In step (2), the ball milling speed is 400-500 r / min, and the ball milling time is 20-30 min; In step (2), the specific surface area of ​​the solid waste cementitious material is greater than 450 m 2 / kg.

9. The preparation method according to claim 6, wherein The preparation of the composite admixture comprises the following steps: The polycarboxylate water reducer and sodium polyoxyethylene fatty alcohol ether sulfate are weighed in proportion, dispersed in deionized water, fully mixed, dried, and the solid is collected and mixed with maltitol and hydroxypropyl methylcellulose in proportion, and ball milled to obtain a composite admixture.

10. The preparation method according to claim 6, wherein The premixing time is 3-6 min, and the speed is 40-60 r / min; The first stirring time is 6-8 min, and the speed is 40-60 r / min; The second stirring time is 2~3 min, and the speed is 40~60 r / min.

Citation Information

Patent Citations

  • Method for reducing self-constriction of ultra-high performance concrete, high-strength concrete and high-strength mortar

    CN115490448A

  • Solid waste filling material based on fine-fraction gold tailings and preparation method of solid waste filling material

    CN119019128A

  • Ultra-high performance concrete containing graphite tailing fine aggregate and preparation method thereof

    CN119100705A

  • Gold tailing-based alkali-activated ultra-high performance concrete and preparation method thereof

    CN119954442A

Cited By

  • Early strength agent as well as preparation method and application thereof

    CN121494386A

  • Early strength agent, its preparation method and application

    CN121494386B

  • Production process of high-strength concrete based on nano silicon dioxide and polypropylene

    CN122277216A